"Immunolocalization and effect of low concentrations of Insulin like growth factor‐1 (IGF‐1) in the canine ovary". Issue 1 (7th September 2020) - Cardilli, Diogo J.; Sousa‐Oliveira, Kellen; Franchi‐João, Carolina; Azevedo‐Voorwald, Faviana; Machado‐Silva, Marco A.; Oliveira, João Ademir; Sánchez‐Calabuig, María Jesús; Toniollo, Gilson H.; Pérez‐Gutiérrez, José F.
Abstract: Insulin like growth factor‐1 (IGF‐1) plays an important role in the regulation of ovarian function. Despite its extensive study in several species, there is a paucity of information about IGF‐1`s function and localization in the canine ovary. The aim of the present study was to assess the effect of IGF‐1 on oocyte nuclear maturation and to immunolocalize the IGF‐1 and its receptor (IGF‐1R) in the ovary. Cumulus‐oocyte complexes (COCs) were obtained from 34 bitches. The COCs from each bitch were incubated in TCM 199‐HEPES in the absence ( n = 199) or presence ( n = 204) of 100 ng/ml IGF‐1 for 96 hr at 38ºC in 5% CO2, stained and evaluated for nuclear maturation by fluorescence microscopy. The results showed that the addition of IGF‐1 did not have an effect ( p ˃ 0.05) on the nuclear maturation under these conditions. The immunohistochemical study revealed nuclear and cytoplasmic staining for IGF‐1 and IGF‐1R, respectively. Both were localized in all ovarian structures including the corpus luteum, but not in the granulosa cells from primordial follicles. In addition, IGF‐1 was not localized in the oocytes in tertiary follicles. The results obtained show the presence of IGF‐1 through the stages of follicular growth and in the corpus luteum of the canine ovary. However, its role on oocyte nuclear maturation could not be demonstrated. Abstract : The Insulin like growth factor‐1 (IGF‐1) was localized by immunohistochemistry in the canine ovary from 34 bitches. IGF‐1 and IGF‐1R were localized in all ovarian structures including the corpus luteum, but not in the follicular cells from primordial follicles in the canine ovary. The results showed that the addition of IGF‐1 at 100 ng/ml did not have effect ( p ˃ 0.05) on the nuclear maturation.